Effects of ethanol and phenobarbital treatments on the pharmacokinetics of toluene in rats. - Wang, R S (1992)
Rats were exposed to toluene at a wide range of concentrations from 50 to 4000 ppm for six hours, and the effects of ethanol and phenobarbital (PB) treatments on the pharmacokinetics of toluene metabolism were investigated. Ethanol treatment influenced toluene metabolism mainly at low exposure concentrations. Thus ethanol accelerated the clearance of toluene from blood only when the blood concentration of toluene was not high (less than 360 microM), and ethanol increased hippuric acid (HA) excretion in urine more significantly at low (less than 250 ppm) than at high atmospheric toluene concentrations. Ethanol also expressed a similar effect on p-cresol excretion as on HA, but had little effect on o-cresol. Phenobarbital treatment promoted the urinary excretion of all of the metabolites of toluene, especially after exposure to high toluene concentration. As well as HA, benzoylglucuronide (BG) and free benzoic acid were found in urine. These are the products of the side chain metabolism of toluene. Amounts of BG could be detected when the urinary excretion of free benzoic acid exceeded 5 mumol/kg/6 h, indicating that a great deal of benzoic acid is required for the formation of BG. The Michaelis constant (Km) and the maximum rate of metabolic excretion in urine during six hours exposure (Vmax) of isozymes involved in the excretion of toluene metabolites were calculated, and correlated with the subtypes of cytochrome P-450. The significance of the result was suggested in the biological monitoring of exposure to toluene.